Proceso de Atención de Enfermería en paciente de sexo femenino de 36 años de edad con fractura de radio distal izquierdo. - Zumba Ormaza, Madeline Thalya (2023)
This clinical case concerns nursing care in a patient who is undergoing a fracture of the distal radius, which is undergoing surgery. This clinical case reinforces the knowledge acquired during vocational training. We aim to provide quality care with warmth to guarantee the effectiveness of comprehensive care for this type of patient, through appropriate interventions based on the NANDA, NOC and NIC classifications, based on scientific and practical criteria in the patient and also to educate not only the patient but also their family members about the subsequent care after discharge from the hospital. Distal radius fractures are one of the most frequent reasons for consultation in the emergency rooms of the IESS Babahoyo Hospital. For this type of fracture, there are several types of treatment to which the patient may be subjected, depending on the characteristics of the injury. Our nursing care is raised both pre-, intra- and post-surgical. At each stage, the Nursing Care Process was applied, the splint care was performed, medication was administered, physical means were applied that helped to reduce the edema and erythema presented in the patient. The patient's health was always evaluated, with a successful recovery after surgery, since there were no complications at any time and its evolution was favorable. In the last stage of the patient's recovery, our nursing intervention will be the education that we will give to the patient and her family, based on the care she should receive and how to lead her life after hospital discharge, in order to promote her recovery early and expected and to prevent poor care and the appearance of one or more comorbidities in her.